Collecting design - Lindemann, Adam , 1961- (Taschen, 2010)
Insiders' Tips on Your Favorite Design and How to Enjoy and Make Profit. Collecting Design tells all about an addictive occupation, vintage pieces vs. limited editions, the big names and what to keep an eye on, all from the perspective of a passionate collector meeting market luminaries for in-depth conversations-his fellow collectors (Bruno Bischofberger, Michael Boyd, Peter Brant, Dennis Freedman, Reed Krakoff, Ronald Lauder, Rachel Lehmann), the dealers (Anthony DeLorenzo, Suzanne Demisch, Barry Friedman, Cle?mence and Didier Krzentowski, Zesty Meyers and Evan Snyderman, Murray Moss, Patrick Seguin, Alasdhair Willis), select tastemakers (Jacques Grange, Marc Jacobs, Karl Lagerfeld, Peter Marino, Robert Rubin, Ian Schrager, Axel Vervoordt), and auction experts (Philippe Garner from Christie's, Alexander Payne from Phillips de Pury, Richard Wright, James Zemaitis from Sotheby's)